2014
DOI: 10.1002/ajh.23801
|View full text |Cite
|
Sign up to set email alerts
|

Monosomal karyotype is an independent predictor of survival in patients with higher‐risk myelodysplastic syndrome

Abstract: A monosomal karyotype (MK) correlates with poor survival in patients with acute myeloid leukemia, although whether this is also the case in patients with myelodysplastic syndrome (MDS) remains controversial. Some studies report a correlation between a MK and a worse survival, whereas others claim that this correlation arises because of a confounding effect between a MK and a complex karyotype (CK). To address this question, we analyzed the clinical data and karyotypes of 610 adults with MDS. A MK was identifie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
26
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(29 citation statements)
references
References 23 publications
3
26
0
Order By: Relevance
“…Non-transplant studies have shown that MK has more a significant effect on survival compared with that found in other classification systems for complex cytogenetics in MDS. [18, 42, 43] The few recent studies evaluating the importance of MK in alloHCT have reported results similar to ours. In a specific cohort of MDS patients with chromosome 7 abnormalities, Van Gelder et al, using the European Group for Blood and Marrow transplantation (EBMT) database, showed that MK was more predictive of progression-free survival and OS after alloHCT than complex cytogenetics in 261 MDS or AML patients.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Non-transplant studies have shown that MK has more a significant effect on survival compared with that found in other classification systems for complex cytogenetics in MDS. [18, 42, 43] The few recent studies evaluating the importance of MK in alloHCT have reported results similar to ours. In a specific cohort of MDS patients with chromosome 7 abnormalities, Van Gelder et al, using the European Group for Blood and Marrow transplantation (EBMT) database, showed that MK was more predictive of progression-free survival and OS after alloHCT than complex cytogenetics in 261 MDS or AML patients.…”
Section: Discussionsupporting
confidence: 87%
“…Other cytogenetic groupings recognizing the monosomal karyotype (MK) are also found to impact on OS in MDS patients. [18, 19] The molecular/genetic prognostic landscape remains complex in MDS, and it is not clear which prognostic system, the IPSS, R-IPSS, TSCG, or presence/absence of MK, are the most clinically relevant in the setting of alloHCT.…”
Section: Introductionmentioning
confidence: 99%
“…The revised IPSS cytogenetics include very poor cytogenetics as complex (>3) cytogenetic abnormalities which are associated with MK+. Xing et al analyzed outcomes of MDS patients showing complex karyotype and MK+ yielding similar poor outcomes(39). The revised IPSS confirmed poor prognosis for the very poor cytogenetics category (40).…”
Section: Discussionmentioning
confidence: 99%
“…Karyotype analyses were performed on un-stimulated bone marrow cells after 24 h of culture using R-banding techniques [7]. Chromosome identification and karyotype descriptors used the International System for Human Cytogenetic Nomenclature (ISCN) [14].…”
Section: Methodsmentioning
confidence: 99%
“…Cytogenetic analysis provides important diagnostic and prognostic information for patients with MDS and plays an essential role in the International Prognostic Scoring System (IPSS) and the revised International Prognostic Scoring System (IPSS-R)[2–3]. Common cytogenetic abnormalities detected at diagnosis include -7/7q-, -5/5q-, +8, 20q-, -Y, i(17q) or t(17p), -13/13q-, 11q-, 12p- or t(12p), and the most common abnormalities (-7/7q-, -5/5q-, +8 and 20q-) occur in approximately 40% of all MDS cases[4–7]. The gold standard of cytogenetic diagnostics for MDS remains conventional chromosome banding analysis of bone marrow metaphases.…”
Section: Introductionmentioning
confidence: 99%